Berberine Suppresses Colonic Inflammation in Dextran Sulfate Sodium–Induced Murine Colitis Through Inhibition of Cytosolic Phospholipase A2 Activity - Zhai, Lixiang; Huang, Tao; Xiao, Hai-tao; Wu, Pei-gen; Lin, Cheng-yuan; Ning, Zi-wan; Zhao, Ling; Kwan, Hiu Yee Anna; Hu, Xian-jing; Wong, Hoi Leong Xavier; Li, Xian-qian; Bian, Zhao-xiang (Frontiers in Pharmacology, 2020)
Ulcerative colitis (UC) causes chronic inflammation and damage to the colonic mucosal layer. Recent studies have reported significant changes in phosphatidylcholine (PC) and lysophosphatidylcholine (LPC) in UC patients and oral administration of PC has considerable therapeutic effects against UC, suggesting the metabolism of phosphatidylcholine may be involved in the UC development. Our previous work has demonstrated that berberine effectively suppresses inflammation and protects colonic mucosa injury in DSS-induced colitic mice. However, whether the therapeutic effects of berberine is attributed to its action on PC metabolism remains unknown. In the present study, we have shown that berberine significantly reduced the lysophosphatidylcholine (LPC) levels in the sera of DSS-induced experimental colitis mice and LPS-stimulated macrophage RAW 264.7 cells. The cytosolic phospholipase A2a (PLA2G4A), an enzyme for hydrolyzing PC to LPC, was found to be upregulated in the colon tissue of experimental colitis mice and inflamed macrophage RAW 264.7 cells. We then demonstrated berberine inhibited the phosphorylation of cytosolic phospholipase A2a (PLA2G4A) in the colon tissue of experimental colitis mice and inflamed macrophage RAW 264.7 cells. Subsequently, we revealed berberine suppressed the expression of pro-inflammatory factors including TNF-alpha and IL-6 through regulating PLA2G4A dysfunction in macrophage RAW 264.7 cells. Mechanistically, we found that berberine directly binds to PLA2G4A and inhibits MAPK/JNK signaling pathway to inhibit PLA2G4A activity in inflammatory status. Therefore, we concluded that berberine inhibits colonic PLA2G4A activity to ameliorate colonic inflammation in experimental colitic mice, suggesting modulation of PC metabolism via PLA2G4A might be beneficial for establishing new therapies strategy for UC.